Immunohistochemistry: Relevance in dermatology - Aparna Palit; Arun C Inamadar (Wolters Kluwer Medknow Publications, 2011)
Use of immunohistochemical technique is increasing in diagnosing various diseases. In many situations it may not be possible to differentiate entities with overlapping clinical and histopathological features. Immunostaining of cellular antigens is immensely helpful in such cases. Immunohistochemistry (IHC) has also been in use for targeted cancer therapy. In this article, the discussion will be restricted to use of IHC in dermatological disorders and use of classical antigens with brief updating of some important newly discovered antigens.